WORK ENGAGEMENT AS MEDIATION THE EFFECT OF EMPOWERMENT AND TRANSFORMATIONAL LEADERSHIP TO EMPLOYEE PERFORMANCE - Basith Faqih, Abdul; Maharani Ekowati, Vivin (Universitas Islam Lamongan, 2024)
Z workers in Malang City and Empowerment and Transformational Leadership, as well as the mediating function of Work Engagement in this relationship, in order to identify the impact of these factors on Employee Performance. The methodologies utilised in this investigation are quantitative. The study's population consists of one hundred seventy persons from generation Z who work in Malang City. Questionnaires were utilised to collect data, which was then analysed using PLS techniques and SmartPLS version 3. This study found that empowerment and transformational leadership had no meaningful effect on employee performance. The relationship between empowerment and transformative leadership and employee performance may be mediated, in part, by job engagement, but in a more indirect and significant manner.